2008
DOI: 10.1093/hmg/ddn054
|View full text |Cite
|
Sign up to set email alerts
|

FANCM of the Fanconi anemia core complex is required for both monoubiquitination and DNA repair

Abstract: In response to DNA damage, the Fanconi anemia (FA) core complex functions as a signaling machine for monoubiquitination of FANCD2 and FANCI. It remains unclear whether this complex can also participate in subsequent DNA repair. We have shown previously that the FANCM constituent of the complex contains a highly conserved helicase domain and an associated ATP-dependent DNA translocase activity. Here we show that FANCM also possesses an ATP-independent binding activity and an ATP-dependent bi-directional branch-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
137
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(150 citation statements)
references
References 46 publications
11
137
1
1
Order By: Relevance
“…Recently, a human homolog of Mph1, FANCM, was identified as a part of the FA core complex 1 (Meetei et al 2005;Mosedale et al 2005). Initial studies suggested that FANCM protein does not have DNA unwinding activity; however, its helicase domains are required for DNA damage resistance (Xue et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a human homolog of Mph1, FANCM, was identified as a part of the FA core complex 1 (Meetei et al 2005;Mosedale et al 2005). Initial studies suggested that FANCM protein does not have DNA unwinding activity; however, its helicase domains are required for DNA damage resistance (Xue et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Gel Mobility Shift Assay-DNA substrates were prepared by annealing the oligonucleotides ( Table 1) described previously (18,27). Oligonucleotide H1 was synthesized with a 5Ј-Alexa Fluor 488 dye label.…”
Section: Methodsmentioning
confidence: 99%
“…Because ATP hydrolysis by FANCM is dispensable for the monoubiquitination of FANCD2 in vivo (20), it is unclear whether translocation of FANCM on DNA is essential for the FA pathway. The ATPase-mutant protein K117R FANCM, however, fails to complement the sensitivity of FANCM-depleted cells to ICLs (20), indicating that FANCM's translocase activity is required for DNA damage tolerance.…”
mentioning
confidence: 99%